PENGARUH KEPEMIMPINAN BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP DISIPLIN KERJA PADA KARYAWAN PT. BPR TRIDARMA PUTRI DI KABUPATEN KLUNGKUNG - Ade Febriyanti, Ni Luh; Herlambang, Putu Gede Denny (Jurnal MBE Manajemen Bisnis, Equilibrium, 2023)
Developments in the financial sector, especially changes in the composition or structure of the banking system in Indonesia, are expected to bring positive changes to the national economy. Employee discipline in the company must be improved and sustainable, therefore it is necessary to have periodic monitoring and evaluation to ensure that employees who work are always disciplined. Every employee who is a member of the company has a different culture, because they have different cultural backgrounds, but all these differences will unite into one culture, namely organizational culture, to become a group that works together in achieving organizational goals. An employee can be productive at work and be more disciplined if his needs and desires are met, because if it is not matched by motivation, it will be difficult to increase discipline at work. The purpose of this study was to determine the effect of organizational leadership and work motivation on work discipline among employees at PT. BPR Tridarma Putri in Klungkung Regency. The sample in this study were all employees at PT. Tridarma Putri BPR in Klungkung Regency, totaling 57 people. The data analysis technique used is multiple linear regression coefficient analysis, determination analysis, t-test and F-test, using the help of a computer program (SPSS) Version 26.00 for Windows. The results of the analysis show that 1) Leadership, organizational culture and motivation partially have a positive and significant effect on work discipline. 2) Leadership, organizational culture and motivation simultaneously have a positive and significant effect on work discipline.